Effects of biochar, compost, and composted biochar soil amendments on okra plant growth - Azman, Nur Aina Najwa Mohd Nor; Khalid, Puteri Inderakusumowati Md; Amin, Nor Aishah Saidina; Zakaria, Zaki Yamani; Zainol, Muzakkir Mohammad; Ilham, Zul; Phaiboonsilpa, Natthanon; Asmadi, Mohd (My University, 2022)
Soil fertility can be improved by incorporating organic matter such as biochar and compost. The combined addition of biochar and compost effectively restores soil degradation by enhancing nutrient availability, soil aggregation, and porosity. Nonetheless, many studies mainly concentrated on a single application of biochar and compost as a soil amendment. In this work, the biochar samples were prepared from oil palm empty fruit bunch (OPEFB) material at the desired microwave power (450 W) under 1 L/min of N2 flow for 10 min. Then, sandy soil was amended with 5 g of sole biochar and compost, as well as a biochar-compost mixture at a ratio of 1:1 for 8-weeks polybag experiment of okra plants. At 4 weeks of the plantation, the physical and chemical soil properties were analyzed. The okra plant's growths were also measured weekly for 8 weeks of the plantation. The application of biochar and composts alone, and in combination significantly improved soil physicochemical properties and plant growth compared to control soil. The synergetic positive effect of biochar and compost combination resulting lowered soil bulk density with higher soil porosity, moisture content, and nutrients availability. The study showed that a biochar-compost mixture is more effective to enhance soil quality over individual treatments and unamended soil.
Keywords: Biochar; Compost; Plant growth; Soil amendments; Soil physicochemical properties